Analisis Determinan Pajak Daerah Dan Pengeluaran Pemerintah Terhadap Pertumbuhan Ekonomi Di Kabupaten Aceh Utara Tahun 2009-2017 - Rika Sukma; Cut Putri Sari (Jurnal Ekonomi Regional Unimal, 2020)
This study aims to determine the effect of local taxes and government expenditures on economic growth in the North Aceh Regency. This study uses secondary data in the form of time series data in 2009-2017 obtained from the Central Bureau of Statistics of Aceh Regency. The data analysis method used is the Multiple Linear Regression analysis. The result partially shows that local taxes have a positive and significant effect on economic growth in North Aceh Regency, while government expenditures have a negative and significant effect on economic growth in North Aceh Regency. Simultaneously, local taxes and government spending have a significant effect on economic growth in the North Aceh Regency. Keywords: Economic Growth, Local Taxes and Government Expenditures